From Volatile Ethanolamine to Highly N, B Dual Doped Carbon Superstructures for Advanced Zn-Ion Hybrid Capacitors: Unveiling the Respective Effects Heteroatom Functionalities. Issue 7 (1st July 2022) - Wang, Dewei; Zhang, Zhao; Sun, Jiaqi; Lu, Zeming
Abstract : Understanding the active sites of heteroatoms in carbon matrix is highly desired to design advanced Zn-ion hybrid capacitors (ZICs) with high charge storage capability. Herein, N, B dual doped carbon nanosheet covering network (BN-SCN) superstructures were successfully prepared by simply pyrolysis of volatile ethanolamine in the presence of boric acid. The intermediated product formed between ethanolamine and boric acid can prevent the ethanolamine from evaporating during the pyrolysis process. Benefiting from the N and B enriched reactants, the resulting samples have a high level of heteroatoms (6.04 at % B and 9.73 at % N), which afford sufficient pseudo-capacitance to boost the specific capacity. Consequently, the as-assembled aqueous ZIC device yielded a high capacity of 133.8 mAh g −1 at 0.1 A g −1, high specific energy of 107 W h kg −1, and an outstanding power output of 16 kW kg −1 . The ex situ XPS analysis results confirm a reversible transformation of the configuration of oxygen functional groups, which can offer additional pseudo-capacitance. Except for nitrogen functional groups, the presence of abundant B containing functional groups can further enhance the chemical absorption/desorption of Zn 2+ ions.